2014
DOI: 10.3389/fnsys.2014.00117
|View full text |Cite
|
Sign up to set email alerts
|

Comparative organization of the claustrum: what does structure tell us about function?

Abstract: The claustrum is a subcortical nucleus present in all placental mammals. Many anatomical studies have shown that its inputs are predominantly from the cerebral cortex and its outputs are back to the cortex. This connectivity thus suggests that the claustrum serves to amplify or facilitate information processing in the cerebral cortex. The size and the complexity of the cerebral cortex varies dramatically across species. Some species have lissencephalic brains, with few cortical areas, while others have a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 78 publications
9
42
0
Order By: Relevance
“…According to our findings we can hypothesize either that this structure is not part of the claustrum or that it is a part of the posterior claustrum. This latter hypothesis might be in line with the discontinuities described by Baizer et al (2014) in the claustrum of animals with large brains although in the histological sections we did not find a clear discontinuity between the claustrum and the cloud of neurons. However, following the former hypothesis, these neurons might represent the posterior extent of the insular pocket.…”
Section: Histologysupporting
confidence: 90%
See 1 more Smart Citation
“…According to our findings we can hypothesize either that this structure is not part of the claustrum or that it is a part of the posterior claustrum. This latter hypothesis might be in line with the discontinuities described by Baizer et al (2014) in the claustrum of animals with large brains although in the histological sections we did not find a clear discontinuity between the claustrum and the cloud of neurons. However, following the former hypothesis, these neurons might represent the posterior extent of the insular pocket.…”
Section: Histologysupporting
confidence: 90%
“…Moreover, in the light of recent anatomical studies (Baizer et al, 2014;Johnson et al, 2014) we analyzed the histological features of this enigmatic structure. Although many immunohistochemical studies have shown the presence of PV in the claustrum of different animals 1 Dachshund 11 Female 11 64 Intra-abdominal hemorrhage 2 Fox terrier 12 Male 10 66 Peritonitis 3 Mixed-breed 4 Male 14.5 70 Trauma 4 Mixed-breed 9 Male 16 72 Heart failure * Formalin fixed.…”
mentioning
confidence: 99%
“…Nevertheless, it is generally accepted today that the claustrum exhibits widely distributed reciprocal anatomic projections to virtually all regions of the cortex as well as to many subcortical structures, including the hippocampus, amygdala, and caudate nucleus. Substantial evidence now exists that the major target of claustral projections is the cortex, and that the major input to the claustrum comes from the cortex (see reviews by Smythies et al, 2012Smythies et al, , 2014Baizer et al, 2014;Mathur, 2014;Torgerson and Van Horn, 2014).…”
Section: H a Role For The Claustrum?mentioning
confidence: 99%
“…Although Crick and Koch (2005) proposed that the claustrum might mediate consciousness, or provide perceptual integration across sensory modalities, Baizer et al (2014) argue against this hypothesis, stating that intraclaustral processing would require that the claustrum be a continuous structure, which it is not in every species. Furthermore, as the cortex has expanded through evolution in different species, the size of the claustrum has actually decreased in relative size (Kowianski et al, 1999).…”
Section: H a Role For The Claustrum?mentioning
confidence: 99%
“…This strong connectivity is unsurprising given the vast cortical connections of the claustrum itself. Because its function is still unknown, with suggestions ranging from the simple facilitation of cortical function (Baizer et al, 2014), to the basis of consciousness (Crick and Koch, 2005), it is difficult to speculate as to the role this anatomical connection might have.…”
Section: Discussionmentioning
confidence: 99%